2021
DOI: 10.1029/2020jb020265
|View full text |Cite
|
Sign up to set email alerts
|

The Mabja Dome Structure in Southern Tibet Revealed by Deep Seismic Reflection Data and Its Tectonic Implications

Abstract: The ongoing India‐Asia collision has led to the formation of the northern Himalayan gneiss domes belt in southern Tibet. The domes are the result of the ongoing convergence and were formed by geological processes that may include crustal thickening, metamorphism, partial melting, and exhumation of middle crustal rocks to the surface. A combination of compressional, extensional, and diapiric processes has been invoked to explain the formation and evolution of these domes. Differentiating among these competing h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 114 publications
0
3
0
Order By: Relevance
“…Liu et al (2006) confirmed that the dip angle of the mid-crustal reflection formed by the Main Himalayan Thrust (MHT) increases progressively with its northward extension and that the MHT continues north of the Kangmar dome. The thrust stacking above the MHT detected by the most recent Frontiers in Earth Science frontiersin.org regional N-S trending seismic profile (Li et al, 2021) between the Mabja dome and Kampa dome was interpreted as the cause of the doming event. However, the GKT was not observed at the corresponding depth in either seismic profile, and the STDS was identified at a depth of 3-3.5 km as a continuous interface overlying the high-velocity body and extending northward for a considerable distance (Figure 10D).…”
Section: Evolution Of the Dome And Its Implicationsmentioning
confidence: 96%
See 1 more Smart Citation
“…Liu et al (2006) confirmed that the dip angle of the mid-crustal reflection formed by the Main Himalayan Thrust (MHT) increases progressively with its northward extension and that the MHT continues north of the Kangmar dome. The thrust stacking above the MHT detected by the most recent Frontiers in Earth Science frontiersin.org regional N-S trending seismic profile (Li et al, 2021) between the Mabja dome and Kampa dome was interpreted as the cause of the doming event. However, the GKT was not observed at the corresponding depth in either seismic profile, and the STDS was identified at a depth of 3-3.5 km as a continuous interface overlying the high-velocity body and extending northward for a considerable distance (Figure 10D).…”
Section: Evolution Of the Dome And Its Implicationsmentioning
confidence: 96%
“…Note that the detachment of the STDS persisted, and the YGR became active at some approximate later time. (C) Continued fast cooling due to glacier activity; (D) interpretation of the deep seismic reflection profile image byLi et al (2021). R1-R5 are relatively high reflections.…”
mentioning
confidence: 99%
“…In the past few decades, FWI has been successfully applied to active‐source ocean‐bottom and streamer datasets to characterize the oceanic crustal structures (e.g., Górszczyk et al., 2017, 2021; Gray et al., 2019; Kamei et al., 2012; Morgan et al., 2016; Operto et al., 2006; Ravaut et al., 2004), and the land datasets to characterize the continental structures (e.g., Bleibinhaus et al., 2007; Morgan et al., 2011). In particular, FWI has also been applied to deep reflection seismic profiles in the study of the upper‐crustal structures (Adamczyk et al., 2015; Li, Gao, et al., 2021; Smithyman & Clowes, 2013; Zhang et al., 2021). Still, the application of FWI to the field data faces considerable difficulties, as FWI is an inverse problem with strong nonlinearity (e.g., Virieux & Operto, 2009) and prone to suffer from ill‐posedness originating from the crosstalk between different parameters.…”
Section: Introductionmentioning
confidence: 99%